PEMANFAATAN BARANG BEKAS SEBAGAI BAHAN PRAKTIKUM PEMBELAJARAN SBK MATERI KERAJINAN BAGI GURU-GURU SDN IV KOTO KABUPATEN AGAM - Syafwan Syafwan; Yunisrul Yunisrul; Syafei Syafei; Zubaidah Zubaidah; Irwan Irwan; Mediagus Mediagus (Ranah Seni, 2018)
Teachers in Elementary School Subdistrict IV Koto Agam District, especially Elementary School Gugus 01 Subdistrict IV Koto Agam experienced problems in the implementation of learning Arts and Skills Arts (SBK), especially craft materials. The reality that exists in the elementary school is that SBK learning is not well implemented. The main problem is that teachers do not master SBK material, especially craft materials. Based on these problems it was agreed with the Chairperson of Cluster 1 District IV Koto, that the priority issues to be resolved were concerning; 1) mastery of craft learning materials and 2) mastery of craft-making techniques from used goods. To overcome this problem, training was carried out to teachers, with the aim of increasing teacher mastery in craft learning, so as to improve the quality of SBK learning, especially craft material in Elementary School. The results of these activities are: Most of junior high school teachers have mastered the craft materials given, especially the technique of making handicrafts from used goods properly.